Fitting of Removable Dentures in Schizophrenic Patient Complicated with Tardive Dyskinesia - Suwannee Toomtong, D.D.S. (Journal of The Department of Medical Services, 2021)
We report a schizophrenic patient who developed involuntary movement of her mouth and tongue during a dental visit. Tardive dyskinesia was suspected from her antipsychiatric medications, then her psychiatrist was consulted and notified about her concurrent symptoms. The dental management includes tooth extraction, prosthodontic treatment including single maxillary denture and lower partial removable acrylic denture with non anatomical teeth to minimize lateral force and improved stability. Denture adhesive is employed to increase retention of the maxillary denture. The result shows a satisfaction of mastication and recovery of facial esthetic. Both the dentist and patient are very satisfied with the treatment.